Small and medium-sized enterprises, global value chains, and circular economy - Acosta Santos, Ariadna Alejandra (2025)
This study aims to analyze the role of small and medium-sized enterprises in Nuevo León in managing waste within the global value chain. The researchers interviewed a non-random sample of 20 SMEs. The findings revealed that these SMEs are actively involved in international trade and are part of global supply networks. Furthermore, these SMEs participate in industrial symbiosis by using waste from other enterprises as inputs in their production processes. These practices are generally informal and spontaneous, driven primarily by the aim of reducing material costs. However, there is potential to formalize and integrate these strategies into a sustainable production agenda.